Assessment of 137Cs in the Environment of Hetauda City, Nepal by In-Situ Gamma Ray Spectrometry - A. Mishra; R. Khanal (National Research and Innovation Agency, 2023)
A significant amount of 137Cs radioactive fallout have been spread in the atmosphere due to nuclear weapon testing and nuclear reactor disasters. This fallout eventually settles on the Earth's surface, and because 137Cs has a long half-life, it remains in the environment for an extended period. Mapping the distribution of 137Cs is crucial, and this study aims to assess the radioactive deposition of 137Cs in the ground to establish baseline data for its distribution in the environment of Hetauda City, Nepal. Recently, Hetauda City has been designated as the capital city of the Bagmati province. To measure 137Cs deposition, portable (backpack) gamma ray spectrometer was used with a 0.347-liter NaI(Tl) detector. Rapid measurement was carried out while walking at a pace of less than 2 km/h, and the distance between the detector and the ground was maintained at less than 1 m with the detector pointing downward. The surface activity of 137Cs was measured in the range of 0.003 to 2.382 kBq/m2, with an average value of 0.581 ± 0.343 kBq/m2. The spatial variability of 137Cs was found to be smooth in the area, and the mean annual effective dose calculated was 0.379 ± 0.224 µSv. The low dose rates and smooth spatial distribution of 137Cs in the environment indicate no contamination, and the trace amount present could be due to global fallout from weapons testing and nuclear accidents. The results were compared with previously reported values worldwide.